2018
DOI: 10.1590/0034-7167-2017-0360
|View full text |Cite
|
Sign up to set email alerts
|

Perception of cancer patients in palliative care about quality of life

Abstract: The results indicate that the concept of quality of life is subjective, tied to personal values and influenced by the repercussions of the health-disease process. In addition, they can guide actions based on interdisciplinary assistance aimed at the real needs of these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
31

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 24 publications
0
19
0
31
Order By: Relevance
“…In this scenario, a careful evaluation allows the promotion of quality of life to the ill subject. 12 In general, it is observed that aggravation of symptoms and diseases at advanced stages with no possibility of cure have a strong impact on the structure and family dynamics of patients. 13 Therefore, according to CSDs corresponding to the central ideas 1 and 2, it is important to highlight that family members or caregivers were not considered targets of PC, which is a major obstacle to the good practice of this philosophy.…”
Section: Resultsmentioning
confidence: 99%
“…In this scenario, a careful evaluation allows the promotion of quality of life to the ill subject. 12 In general, it is observed that aggravation of symptoms and diseases at advanced stages with no possibility of cure have a strong impact on the structure and family dynamics of patients. 13 Therefore, according to CSDs corresponding to the central ideas 1 and 2, it is important to highlight that family members or caregivers were not considered targets of PC, which is a major obstacle to the good practice of this philosophy.…”
Section: Resultsmentioning
confidence: 99%
“…A diminuição da qualidade de vida entre pacientes oncológicos pode estar vinculada a diversas condições, como mudanças físicas e emocionais, dor, dependência de terceiros, perda da autoestima, e ao estigma culturalmente atrelado a essa morbidade 23 . A prevalência de transtorno depressivo no âmbito de pacientes oncológicos é maior do que aquela encontrada na população geral e essas proporções variam expressivamente entre os estudos em razão da escolha de amostras específicas e do uso de métodos de avaliação distintos 24 .…”
Section: Discussionunclassified
“…The presence of cancer signi cantly deteriorates QOL [10,11]. In Ahlam et al study, it was shown that, the majority of Moroccan patients with advanced palliative care experienced deteriorated QOL in all aspects of physical and emotional functioning [12].…”
Section: Introductionmentioning
confidence: 99%